Corticokinematic coherence as a new marker for somatosensory afference in newborns. Issue 4 (April 2017) - Smeds, Eero; Vanhatalo, Sampsa; Piitulainen, Harri; Bourguignon, Mathieu; Jousmäki, Veikko; Hari, Riitta
Highlights: We analyzed coherence between EEG and passive finger and wrist movements in newborns. In all newborns, EEG of the contralateral central scalp was coherent with the movements. Passive movements could be used to assess somatosensory function in neonatal intensive care. Abstract: Objective: Somatosensory evoked potentials have high prognostic value in neonatal intensive care, but their recording from infants is challenging. Here, we studied the possibility to elicit cortical responses in newborns by simple passive hand movements. Methods: We examined 13 newborns (postnatal age 1–46 days) during clinically indicated 19-channel electroencephalography (EEG) recordings in the neonatal intensive care unit; EEG indications included birth asphyxia and suspected epileptic seizures. The experimenter moved the infant's wrist or fingers at 1 or 2 Hz for 5–10 min, separately on both sides. We measured movement kinematics with an accelerometer attached to the infant's hand and computed coherence between the EEG and acceleration signals (corticokinematic coherence, CKC). Results: Statistically significant CKC (amplitude 0.020–0.511) with characteristic scalp topography was observed in all infants at twice the movement frequency. CKC was contralaterally dominant on the central scalp (median laterality index 0.48 for right-hand and −0.63 for left-hand movements). Conclusions: Passive movements elicit cortical responses that can be readily observed in clinical EEG recordings from newborns in the intensive-care environment. Significance: CKC is a novel, noninvasive marker for the somatosensory system. Its robustness and practical ease make it attractive for bedside assessment of neurologically compromised newborns.